Effects of Soybean Meal Level on Growth Performance of 25- to 50-lb Nursery Pigs - H. S. Cemin; M. D. Tokach; S. S. Dritz; J. C. Woodworth; J. M. DeRouchey; R. D. Goodband (Kansas Agricultural Experiment Station Research Reports, 2019)
Four experiments were conducted to determine the effects of increasing soybean meal (SBM) level in diets with or without 25% distillers dried grains with solubles (DDGS) on growth performance of nursery pigs raised in university or commercial facilities. Treatments were arranged in a 2 × 3 factorial with main effects of SBM (27.5, 32.5, or 37.5% of the diet) and DDGS (0 or 25% of the diet). A total of 296, 2,502, 4,118, and 711 pigs initially 23.2, 25.7, 27.5, and 27.1 lb body weight (BW) were used in Exp. 1, 2, 3, and 4, respectively. There were 10, 16, 13, and 12 replicates per treatment in Exp. 1, 2, 3, and 4, respectively. After weaning, pigs were fed common diets for approximately 21 d. Then, pens of pigs were assigned to treatments in a randomized complete block design with BW as the blocking factor and experimental diets were fed for 21 d. Pigs were weighed and feed disappearance measured to calculate average daily gain (ADG), average daily feed intake (ADFI), feed-to-gain ratio (F/G), and caloric efficiency (CE). Pigs used in all experiments did not undergo major health challenges during the experimental period and due to the low number of mortality and cull events, statistical analysis was not performed on these variables. The average cull rate was 0.7, 0.5, 0.2, and 0% and the mortality rate was 0.7, 0.3, 0.4, and 0% in Exp. 1 to 4, respectively. There were interactions (P≤ 0.031) between SBM and DDGS for F/G and CE in Exp. 2 and for ADG and ADFI in Exp. 3. These were mostly driven by increasing SBM negatively affecting performance in a greater magnitude when diets contained DDGS compared to diets without DDGS. The main effects of DDGS and SBM were more consistently observed across experiments. Pigs fed diets with 25% DDGS had decreased (P≤ 0.001) ADG and ADFI in all experiments as well as poorer (P≤ 0.025) F/G and CE except for Exp. 3. Feeding increasing amounts of SBM generally did not result in any major impact in ADG, but consistently improved (linear,P≤ 0.078) F/G and CE across experiments. The mechanism for this response is unclear but could be driven by intrinsic components of SBM, such as isoflavones, or by underestimation of SBM energy value.
Keywords: caloric efficiency; growth; protein; soybean meal; swine